Título Padrão - Joly, A. B.; Pinheiro, F. C.; Ferreira, M. M. (Arquivos de Ciências do Mar, 2018)
This paper, following the previous ones of this series (see Joly 1956 , Joly and col. 1962 , 1963 , 1965 , 1965a , 1966 , 1967 , 1987a) , is a report of four marine algae found for the first time along the Brazilian shores. Some of these new recordes were obtained durlng the extensive exploration of the Brazilian coasts made possible by a grant from the John Simon Guggenheim Memorial Foundation. These records represent an antecipation of more detailed florlstics studies that are under preparation.